2013
DOI: 10.1890/13-0152.1
|View full text |Cite
|
Sign up to set email alerts
|

Fiddler crabs facilitate Spartina alterniflora growth, mitigating periwinkle overgrazing of marsh habitat

Abstract: Ecologists have long been interested in identifying and testing factors that drive top-down or bottom-up regulation of communities. Most studies have focused on factors that directly exert top-down (e.g., grazing) or bottom-up (e.g., nutrient availability) control on primary production. For example, recent studies in salt marshes have demonstrated that fronts of Littoraria irrorata periwinkles can overgraze Spartina alterniflora and convert marsh to mudflat. The importance of indirect, bottom-up effects, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 61 publications
4
54
1
Order By: Relevance
“…Top‐down effects also profoundly affect rocky intertidal food webs and can interact with abiotic stressors to impact saltmarsh communities (Paine ; Gittman & Keller ). Our observational data lead us to hypothesize that predation by crustaceans and gastropods likely played a significant role in generating differences among depth treatments (Johnson & Smee ; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Top‐down effects also profoundly affect rocky intertidal food webs and can interact with abiotic stressors to impact saltmarsh communities (Paine ; Gittman & Keller ). Our observational data lead us to hypothesize that predation by crustaceans and gastropods likely played a significant role in generating differences among depth treatments (Johnson & Smee ; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, research showed that burrows created by fiddler crabs (Uca pugnax) increased soil drainage, soil oxidation-reduction potential (that Helps promote beverage sales and to raise awareness for the conservation of tiger quolls [72] is, tendency to acquire electrons; a common measure of water quality), and belowground decomposition of plant debris, which in turn led to significant increases to the primary productivity of the saltmarshes (Figure 1) [27]. Recently, fiddler crabs have proven to be so effective at promoting saltmarsh growth that they alone can compensate for herbivory from marsh periwinkles (Littoraria irrorata) that would otherwise demolish the habitat [28]. Fiddler crabs are also now known to dramatically increase leaf production, trunk diameter and height of mangrove trees, providing a substantial boost to their ecosystem services [29,30].…”
Section: Regulating Ecosystem Servicesmentioning
confidence: 99%
“…Benthos is an important feeding environment for many marine species (Anderson and Lovvorn, 2008;MacDonald et al, 2012;Gittman and Keller, 2013) and a recent study has shown marine benthic species ingest microplastics (Courtene-Jones et al, 2017). Knowledge of the harmful effects of microplastics on benthic marine species and communities is growing (Green, 2016;Galloway et al, 2017), however, little is known of past microplastic accumulation in benthic environments.…”
Section: Introductionmentioning
confidence: 99%